A Retrospective Study on the Health Problems of Falcons in Al Ain, United Arab Emirates - Abdullah Al Hemeiri, Maryam; Mohteshamuddin, Khaja; Arias de la Torre, Abraham; Adenew Degafa, Berhanu; Ameni, Gobena (Emirates Journal of Food and Agriculture, 2022)
Falcons are important animals in sociocultural events of the society of the United Arab Emirates (UAE). Like any other birds, falcons can be affected by different health problems. This study was conducted to investigate the major health problems of falcons presented to the City Vet Clinic in Al Ain during 2019